Implementation of E-Learning in English for Islamic Education Learning at Islamic Education Study Program during the Covid-19 Pandemic - Muhammad Zuljalal Al Hamdany (Institut Agama Islam Negeri Palopo, 2021)
Covid-19 has been declared as a global pandemic by WHO. It affects all aspects of humans’ life, including their education. Teaching and learning processes during the pandemic of Covid-19 are done online or by implementing e-learning. This is to avoid the contact among people. This study aims to find out the media used to do e-learning, the consideration in picking the media, as well as the advantages and disadvantages found during the implementation of e-learning. This research involved 6 English lecturers teaching in some tourism vocational universities in Bali. Data of the research were gained through online questionnaires. Then the data were analysed by finding the percentages as well as describing them. It is found that (1) Google Classroom is used by most od the respondents to do e-learning, then followed by Zoom, Edmodo, WhatsApp, and YouTube, (2) accessibility, communication feature, media supported, the provided assessment types, design, and the pricing and budget are the consideration for respondents in picking the e-learning media, (3) the inequality of internet access is the biggest challenge faced by the lecturers in implementing e-learning, but they found that it provides a flexibility in terms of time and spaces.